Arts and health promotion : Tools and bridges for practice, research and social transformation - Corbin, J. Hope (2021)
As a scientific discipline, health promotion has expanded beyond its earlier roots of one-way information dissemination in health education into to a broader, more inclusive approach that considers community perspectives. Since the Ottawa Charter, the field of health promotion has been evolving at a rapid pace, as our understanding of human behavior has deepened; our policy and programs have become more nuanced. The Charter, and subsequent global agreements and frameworks, has further expanded our work and led to the current emphasis on the Social Determinants of Health in designing and developing health-promoting settings, initiatives, and policies. The potential of the Arts as a powerful force to guide and influence health promotion offers endless possibilities to reach and engage the public in new and creative action around health-related issues and well-being. In its myriad forms (painting, plays, photography, song, etc.), the Arts provide a solid medium through which the fusion of culture as well as equity and human rights concerns can be integrated into health promotion policy and practice. Artistic approaches serve the social justice aims of health promotion by providing tangible means to facilitate the amplification of sidelined “voices” and increasing the visibility of invisible or hidden aspects of health and well-being. This book, Arts and Health Promotion: Tools and Bridges for Practice, Research, and Social Transformation, positions the transformative role of the co-creation of knowledge and illustrates how various creative forms of expression have been applied and can be advanced into an important new dimension of health promotion. Filled with rich examples using different art forms to promote health through practice, research, and social mobilization, this book is a “must read” for policymakers and field practitioners. It is also an excellent resource for students, researchers, and scholars, as preparation for the next generation of health promoters.